Efektivitas Ekstrak Bunga Rosella (Hibiscus Sabdariffa L.) Sistemik Terhadap Penyembuhan Ulser Pada Tikus Wistar (Rattus Norvegicus) - Nindita Cahya Mumpuni; Iin Eliana Triwahyuni; Pujiana Endah Lestari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2021)
Ulcer is an open lesion in the oral mucosa which is generally triggered by various causes including trauma, hormonal, infectious agents, nutritional deficiencies, and various other systemic abnormalities. Treatment is needed to prevent secondary infections, reduce inflammation, reduce pain and speed healing. Rosella efficacious to increase endurance, anti-inflammatory, antibacterial and antioxidant. This ability is obtained from flavonoids, tannins, phenols, anthocyanins and saponins. The purpose was to determine the effect of systemic rosella extract on healing time and ulcer diameter and to determine the effective dose of rosella extract on ulcer healing in wistar rats. 20 rats were ulcered on the left buccal by heating the amalgam stopper over the Bunsen fire for 30 seconds and touching for one second then waiting for 48 hours. All groups were condensed with the Vitamin C group (K+), the untreated group (K-) and the treatment group which consisted of 0.17 mg/gBB(P1), 0.33 mg/gBB(P2), and 0.66 mg/gBB(P3). The treatment is done twice a day and the measurement of diameter by placing a plastic filling instrument along the ulcer is then marked and measured with a digital calipers carried out every day until the ulcer heals. Healing time and decrease in ulcer diameter were faster in the treatment group than in the control group. Fastest ulcer healing in roselle extract dose 0.17 mg/gBB. The conclusion described Roselle extract with a dose of 0.17 mg/gBB gives the most effective effect on ulcer healing.